2018
DOI: 10.1186/s12872-017-0738-4
|View full text |Cite
|
Sign up to set email alerts
|

Early commitment of cardiovascular autonomic modulation in Brazilian patients with congenital generalized lipodystrophy

Abstract: BackgroundMetabolic abnormalities in congenital generalized lipodystrophy (CGL) are associated with microvascular complications. However, the evaluation of different types of neuropathy in these patients, including the commitment of cardiovascular autonomic modulation, is scarce. The objective of the present study was to determine the prevalence of cardiovascular autonomic neuropathy (CAN) in patients with CGL compared with individuals with type 1 diabetes and healthy subjects.MethodsTen patients with CGL, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
(53 reference statements)
5
18
0
1
Order By: Relevance
“…Concerning BSCL, Faria et al [ 5 ] previously showed abnormal autonomic modulation in BSCL patients of our cohort by heart rate variability (HRV) analysis, and this was independent of the presence of metabolic and hemodynamic disturbances. Atypical autonomic modulation was also recently confirmed in BSCL patients from Ceará, a Northeast state located near our patients’ state [ 16 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Concerning BSCL, Faria et al [ 5 ] previously showed abnormal autonomic modulation in BSCL patients of our cohort by heart rate variability (HRV) analysis, and this was independent of the presence of metabolic and hemodynamic disturbances. Atypical autonomic modulation was also recently confirmed in BSCL patients from Ceará, a Northeast state located near our patients’ state [ 16 ].…”
Section: Discussionsupporting
confidence: 75%
“…Several studies showed a decrease in static respiratory pressures in patients with metabolic, renal, and cardiovascular complications [ 30 – 33 ], findings that were also described in BSCL patients [ 3 5 , 16 , 34 ]. All BSCL subjects from our research had diabetes, as shown in Table 1 , which is in accordance with the previously published data from our population [ 3 , 14 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A previous article on cardiovascular autonomic neuropathy in our sample of CGL patients mentioned this mutation in a supplementary table. However, it did not describe the clinical characteristics of these two patients [14].…”
Section: Discussionmentioning
confidence: 96%
“…Patient 1 had severe and early micro-and macrovascular complications detected approximately 5 years after the diabetes diagnosis, as well as end-stage renal disease, autonomic cardiovascular neuropathy and acute myocardial infarction at age 29. Ponte et al [14] observed early commitment of cardiovascular autonomic modulation in 10/20 young CGL patients, detected through abnormalities in cardiovascular autonomic neuropathy tests.…”
Section: Discussionmentioning
confidence: 99%